Enhancing Biocompatibility and Mechanical Properties of Additively Manufactured Porous Gyroid Ti–6Al–4V Implants through Hydroxyapatite Infiltration - Arivazhagan, Adhiyamaan; Mani, Kalayarasan; Kamarajan, Banu Pradheepa; V, Athul Menon; G, Ashish Paul; Venugopal, Neo Tarun (International journal of precision engineering and manufacturing, 2024)
There is an increasing demand for durable metallic implants, particularly among elderly patients undergoing revision surgeries for degenerative bone diseases. Approximately 70–80% of the implants are made of metal. Despite their robustness, metallic implants exhibit a higher Young’s modulus than bone, leading to a stress-shielding effect. Although porous structures in implants aim to mitigate this issue, their porosity compromises overall strength. The present study focuses on the design of porous gyroid Ti–6Al–4V specimens and their fabrication using laser powder bed fusion. Subsequently, hydroxyapatite (HAp) combined with polyamide binders was synthesized using the sol–gel method from precursors and infiltrated into porous specimens to enhance their bio-mechanical compatibility. The X-ray diffraction analysis confirmed the presence of both Ti–6Al–4V and HAp. The Tafel plots revealed that the corrosion rate of the porous specimen infiltrated with HAp was about 0.394 mm/year, which is very minimal considering the prolonged implant lifespan. Furthermore, the results from the compression testing revealed that the average Young’s modulus and compressive strength of HAp-infiltrated specimens were found to be increased by 70% and 7.5% respectively when compared to the non-infiltrated porous gyroid Ti–6Al–4V samples. These findings confirm that the HAp not only enhances osseointegration and tissue growth but also enhances the compressive strength of the porous Ti–6Al–4V metallic implants.